Perceived Causes of Obstetric Fistula and Predictors of Treatment Seeking among Ugandan Women: Insights from Qualitative Research - Nalubwama, Hadija; El Ayadi, Alison M.; Barageine, Justus K.; Byamugisha, Josaphat; Kakaire, Othman; Obore, Susan; Mwanje, Haruna; Miller, Suellen (African journal of reproductive health, 2020)
Many obstetric fistula patients remain untreated or present late to treatment despite increasing surgical availability in Uganda. We explored women‘s perceptions of the cause of their obstetric fistula and their treatment seeking behaviours, including barriers and facilitators to timely care access. In-depth interviews and focus group discussions were conducted from June–August 2014 among 33 women treated for obstetric fistula at Mulago Hospital, Kampala. Data were analysed to describe dimensions and commonalities of themes identified under perceived causes and treatment seeking experiences, and their intersection. Perceived obstetric fistula causes included delays in deciding on hospital delivery, lengthy labour, injury caused by the baby, health worker incompetence, and traditional beliefs. Treatment seeking timing varied. Early treatment seeking was facilitated by awareness of treatment availability through referral, the media, community members, and support by partners and children. Barriers to early treatment seeking included inadequate financial and social support, erroneous perceptions about fistula causes and curability, incorrect diagnoses, and delayed or lack of care at health facilities. Our study supports broad educational and awareness activities, facilitation of social and financial support for accessing care, and improving the quality of emergency obstetric care and fistula treatment surgical capacity to reduce women‘s suffering.